Pendampingan Kegiatan Exstrakurikuler English Public Speaking pada Madrasah Ibtidaiyah di Banyuwangi: English Public Speaking - Moh Mahmud; Adib Ahmada; Khalimatus Sa'diyah (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity aims to increase achievement in English public speaking which is carried out at Madrasah Ibtidayyah or elementary schools to introduce the potential of human resources possessed by students. This activity is an extra-curricular activity that is very helpful for students so that in the future they can communicate and interact with the outside world using an international language, namely English.